Fiscal policy effects in the European Union - Andreas Thams (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper analyzes empirically the impact of fiscal policy on the price level for the cases of Germany and Spain. We investigate whether the fiscal theory of the price level (FTPL) is able to deliver a reasonable explanation for the different performances of the price level in these two countries during recent years. We apply two different approaches. The first is a Bayesian VAR model using sign restrictions to assess the relation between surpluses and public debt. Afterwards, we use a Bayesian regime-switching model to uncover changes in monetary and fiscal policy behavior. The analysis basically shows that in each of the two countries fiscal shocks have a significant impact on the price level. Nonetheless, the FTPL does not deliver a reasonable explanation for the differences in the pattern of inflation between the two countries.
Keywords: E30; E31; E42; E62; E63; 330; Fiscal theory; policy interaction; monetary policy; public debt; price level; Euro area